A prospective and retrospective study of Stoppa procedure (giant prosthetic reinforcement of visceral sac) for recurrent, complex and bilateral inguinal hernias - Koshariya, Mahim; Pandey, Rakesh (International Surgery Journal, 2018)
Background: Managing complex inguinal hernia is always a challenge for surgeons. When recurrent or complex hernia is present it is mandatory to adopt an alternative and different approach for the repair of inguinal hernia to avoid any further complication and recurrence. Primary aim of this study is to assess the usefulness of Stoppa procedure in current situation for treatment of bilateral, complex and recurrent hernias. Methods: A prospective and retrospective study of Stoppa procedure (giant prosthetic reinforcement of visceral sac [GPRVS]) for recurrent, complex and bilateral inguinal hernias was conducted in Department of General Surgery Hamidia Hospital from January 2016 to October 2017 , 30 patients with 27 bilateral and 3 unilateral hernias making total 57 hernial sites including five recurrent hernias (after Lichtenstein repair) were operated by GPRVS for bilateral, recurrent and complex inguinal hernias, were included in study. Results: Four complications were seen. One patient developed seroma which resolved spontaneously, one patient developed superficial wound infection. One patient developed right testicular pain which was relieved after medication. One patient developed pain in groin and right thigh which was present preoperatively also but increased after surgery and was relieved on medication. Risk for recurrence present in 18 patients. No recurrence was observed. Conclusions: Because of the excellent results, ease of the procedure and low complication rate, GPRVS is an effective and good option for bilateral, complex and recurrent inguinal hernias.